(untitled) (Journal on studies and research of academic knowledge, 2010)
The carried out investigation below the title: “ECONOMIC AND FINANCIAL REALITY OF THE CARNIVAL OF ENCARNACION” has as main objective which is to decide with the closest possible approximation, the ECONOMIC AND FINANCIAL REALITY OF THE CARNIVAL OF ENCARNACION, whose data have exclusively academic connotation. THE PERIOD OF REALIZATION of it IS THE YEAR 2010. The focussing of the investigation is developed below the mixed paradigm, Quali-quantitative, with preponderance of the quantitative, and considers two of the aspects WHICH are generated with the realization of the carnivals IN encarnacion: The economic and financial capacitances of the human being. The first one, refered to generate utilities, by means of types of works, are these physical or intellectual, in order to grow and satisfy all or almost all their needs, meanwhile, the financial capacitance, it is the capacitance to face commitments assumed, honor them and prepare to grow. THE AFFECTED UNIVERSE IS COMPOSED of various commercial sectors and citizens who are involved direct and indirectly,with their work, professional services, creative, multiple services, informal work etcetera., who generate revenue with these activities. Were taken in the main social sectors considered direct players of the generating activity of econo-financial movements, to be applied to the data collection instruments, which were analyzed conveniently. This investigation aims to give figures of the event that every year moves to the productive sector of the city of Encarnación.